Aneurysm Sac Dynamics and its Prognostic Significance Following Fenestrated and Branched Endovascular Aortic Aneurysm Repair - Rastogi, Vinamr (2024)
Objective: This study aimed to assess aneurysm sac dynamics and its prognostic significance following fenestrated and branched endovascular aneurysm repair (F/BEVAR). Methods: Patients undergoing F/BEVAR for degenerative complex aortic aneurysm from 2008 to 2020 at two large vascular centres with two imaging examinations (30 day and one year) were included. Patients were categorised as regression and non-regression, determined by the proportional volume change (> 5%) at one year compared with 30 days. All cause mortality and freedom from graft related events were assessed using Kaplan–Meier methods. Factors associated with non-regression at one year and aneurysm sac volume over time were examined for FEVAR and BEVAR independently using multivariable logistic regression and linear mixed effects modelling. Results: One hundred and sixty-five patients were included: 122 FEVAR, of whom 34% did not regress at one year imaging (20% stable, 14% expansion); and 43 BEVAR, of whom 53% failed to regress (26% stable, 28% expansion). Following F/BEVAR, after risk adjusted analysis, non-regression was associated with higher risk of all cause mortality within five years (hazard ratio [HR] 2.56, 95% confidence interval [CI] 1.09 – 5.37; p = .032) and higher risk of graft related events within five years (HR 2.44, 95% CI 1.10 – 5.26; p = .029). Following multivariable logistic regression, previous aortic repair (odds ratio [OR] 2.56, 95% CI 1.11 – 5.96; p = .029) and larger baseline aneurysm diameter (OR/mm 1.04, 95% CI 1.00 – 1.09; p = .037) were associated with non-regression at one year, whereas smoking history was inversely associated with non-regression (OR 0.21, 95% CI 0.04 – 0.96; p = .045). Overall following FEVAR, aneurysm sac volume decreased significantly up to two years (baseline vs. two year, 267 [95% CI 250 – 285] cm3 vs. 223 [95% CI 197 – 248] cm3), remaining unchanged thereafter. Overall following BEVAR, aneurysm sac volume remained stable over time. Conclusion: Like infrarenal EVAR, non-regression at one year imaging is associated with higher five year all cause mortality and graft related events risks after F/BEVAR. Following FEVAR for juxtarenal aortic aneurysm, aneurysm sacs generally displayed regression (66% at one year), whereas after BEVAR for thoraco-abdominal aortic aneurysm, aneurysm sacs displayed a concerning proportion of growth at one year (28%), potentially suggesting a persistent risk of rupture and consequently requiring intensified surveillance following BEVAR. Future studies will have to elucidate how to improve sac regression following complex EVAR, and whether the high expansion risk after BEVAR is due to advanced disease extent.